Histological and cognitive alterations in adult diabetic rats following an episode of juvenile diabetic ketoacidosis: Evidence of permanent cerebral injury. (22nd May 2017) - Glaser, Nicole; Sasaki- Russell, Jennifer; Cohen, Michael; Little, Christopher; O'Donnell, Martha; Sall, Jeffrey
Highlights: Patients with type 1 diabetes may have alterations in cognition. A role for diabetic ketoacidosis (DKA) in causing cognitive changes has recently been suggested. Adult rats exposed to DKA as juveniles have hippocampal astrogliosis and cortical neuron loss. Adult rats exposed to DKA as juveniles also have deficits in associative memory. DKA causes long-term alterations in cerebral microstructure and cognitive deficits in rats. Abstract: Evidence suggests that diabetic ketoacidosis (DKA) may cause subtle cognitive alterations in children but the mechanisms are poorly understood. Acute DKA is associated with reactive astrogliosis and microglial activation in a rat model. Whether these inflammatory changes permanently alter brain histology is unknown. We aimed to determine whether DKA results in permanent alterations in brain histology and whether these changes are associated with cognitive deficits in a rat model. We induced diabetes in juvenile rats with streptozotocin at 4 weeks of age. We induced DKA in one group (n = 21) at 5 weeks of age and compared this group to rats with diabetes without DKA episodes (n = 13). Beginning at 7 weeks, rats underwent a series of cognitive tests to evaluate memory. At 15 weeks, rat brains were harvested and examined using immunohistochemistry (IHC). In tests of novel object recognition and social recognition, both groups performed similarly, however, the DKA group performed more poorly in object-place recognition tests, suggesting alterations in hippocampal function. IHC studies demonstrated increased glial fibrillary acidic protein staining intensity in the hippocampus of DKA rats suggesting astrogliosis, and decreased NeuN positive cell counts in the cortex suggesting neuron loss. These studies demonstrate that DKA results in permanent alterations in brain microstructure in a rat diabetes model. These structural changes are associated with deficits in hippocampal function.